STUDI PERBANDINGAN ANIMASI 360 DERAJAT BERTEMA SEJARAH - Arif Sutrisno (Jurusan Seni dan Desain, Fakultas Sastra, Universitas Negeri Malang, 2021)
To identify general characteristics of historical-themed 360o animation, visual characteristics, and ways of delivering material in historical learning media, this study attempts to compare three historical-themed 360o animations, namely the game trailler Assassin's Creed Syndicate Jack the Ripper, Dinosaurs World 360 VR, and Dunkirk 'Save Every Breath'. This research method is by determine the benchmark focus, planning and research, data collection, implementation, recommendations, and analysis. In general, historical 360o animation uses 3D animation techniques. The flow used tends to be linear with narrative storytelling. The point of view used is first person. The camera movement used is a follow subject. Key Words: Animation 360 Degree, Learning Media, History